Circumstances of injury in childhood and adolescence: current data and epidemiology. (1st March 2011) - Ellsaesser, G; Albrecht, M
Abstract : We investigated the population-related and social aspects of injuries in children and adolescents. In contrast to clinical case studies our focus was on risk groups, injury mechanisms and context of injury. Sources of information used for our study included: Causes of Death Statistics, Hospital Diagnosis Statistics, Child and Adolescent Health Survey, Injury Data Base. We compiled data from the period 1998 to 2007 on unintentional injuries, violence and suicide by age group and sex and included study results on social and ethnic risk factors. Our analysis revealed that injuries display an age-specific dynamic: infants carry a high risk for fatal domestic injuries as well as for injuries due to violence, whereas in adolescents the majority of injuries results from fatal traffic accidents and from suicide. In addition, we found that social factors affected specific mechanisms of injury (eg, scalding) and intention (eg, violence) only. A migration status had an age- and sex-related influence on injury rates.